Validation of commercial DNA tests for beef quality traits - Van Eenennaam, A.L.; Li, J.; Thallman, R.M.; Quaas, R.L.; Gill, C.; Franke, D.E.; Thomas, M.G.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Gene mapping and discovery programs have resulted in the detection of numerous DNA ‘markers’ for various beef cattle production traits. Prior to commercializing genetic markers, it is important to validate their purported effects on the traits of interest in different breeds and environments, and assess them for correlated responses in associated traits. One of the biggest challenges in achieving this objective is the availability of cattle populations with sufficient phenotypic data to assess the association between various traits and newly discovered genetic markers. Results from such validation studies to date have not been widely published and genetic marker tests sometimes may be commercialized prior to the collection of field validation data. In addition, conflicting reports about some commercially available markers, as well as the recognized occurrence of well-proven bulls with a high EPD for a given trait but carrying two copies of the “wrong” (unfavorable) marker for that trait, have made some producers wary of investing in DNA-based testing. Producers want to know whether DNA-based tests perform in accordance with the claims of the marketing company and are interested in third-party, independent validation of these tests. The objective of this study was to validate three commercially-available genetic tests (GeneSTAR Quality Grade8, GeneSTAR Tenderness8, and Igenity TenderGENE9).
Keywords: Beef; Cattle; DNA markers; Beef quality traits